2010
DOI: 10.3724/sp.j.1006.2010.01258
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Rice Resources against Rice Black-Streaked Dwarf Virus and Mapping of Resistant QTL

Abstract: Rice black-streaked dwarf virus (RBSDV) disease become epidemic in Jiangsu and Zhejiang provinces. To screen resistant germplasms and discover new resistance genes/QTLs against RBSDV, we evaluated the resistance to RBSDV in 311 japonica varieties in field test. The results showed that no variety was immune to RBSDV. The disease rate of 24 main japonica varieties grown in Jiangsu province at present was 10.0%-29.0% and that of 71.5% varieties in 287 japonica varieties popularized in Jiangsu before was between 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…Among the five RBSDVD resistance QTLs identified in the present study, four QTLs, including qRBSDV3 WR24 , qRBSDV6 WR24 , qRBSDV9 WR24 and qRBSDV11 WR24, were also located in the same “hot spot” on chromosome 3, 6, 9 and 11. For example, qRBSDV3 WR24 was located in the same chromosome interval with qRBSDV3 (Wang et al., ) and qRBSDV3 9194 (Sun et al., ). qRBSDV6 WR24 and qRBSDV11 WR24 shared the same flank SSR marker with qRBSDV6 and qRBSDV‐11 (Sun et al., ; Zhou et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the five RBSDVD resistance QTLs identified in the present study, four QTLs, including qRBSDV3 WR24 , qRBSDV6 WR24 , qRBSDV9 WR24 and qRBSDV11 WR24, were also located in the same “hot spot” on chromosome 3, 6, 9 and 11. For example, qRBSDV3 WR24 was located in the same chromosome interval with qRBSDV3 (Wang et al., ) and qRBSDV3 9194 (Sun et al., ). qRBSDV6 WR24 and qRBSDV11 WR24 shared the same flank SSR marker with qRBSDV6 and qRBSDV‐11 (Sun et al., ; Zhou et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…qRBSDV3 WR24 , qRBSDV6 WR24 , qRBSDV7 WR24 , qRBSDV9 WR24 and qRBSDV11 WR24 , were detected. Previous studies found that the QTLs conferring RBSDVD resistance were frequently and repeatedly detected on the chromosome 3, 6, 7, 9 and 11 (Duan et al., ; Li et al., ; Sun et al., ; Wang et al., ; Zheng et al., ; Zhou et al., ). Among the five RBSDVD resistance QTLs identified in the present study, four QTLs, including qRBSDV3 WR24 , qRBSDV6 WR24 , qRBSDV9 WR24 and qRBSDV11 WR24, were also located in the same “hot spot” on chromosome 3, 6, 9 and 11.…”
Section: Discussionmentioning
confidence: 99%
“…Among 311 japonica cultivars screened by Wang et al . () to evaluate the level of RBSDD resistance, the disease incidence on plants of 24 widely grown cultivars ranged from 10 to 29%, and no variety was immune. Because the specificity, stability and durability of resistance can change, controlling the virus disease is a challenging task (Lecoq et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, damage caused by SBPH feeding has increased, and serious yield reductions have occurred as a consequence [1–3]. Rice viral diseases, such as rice stripe virus (RSV) and rice black-streaked dwarf virus (RBSDV), transmitted by SBPH, often cause major yield losses [4,5]. Rice stripe disease is one of the most serious rice diseases in China.…”
Section: Introductionmentioning
confidence: 99%
“…However, varieties with single resistance genes are always at risk of their resistance being overcome by new strains of virus. There were no reported sources of high resistance to RBSDV, until recently [5,19]. It is therefore necessary to find additional sources of resistance to RSV and other viruses vectored by SBPH.…”
Section: Introductionmentioning
confidence: 99%